Silencing of Glutathione Peroxidase 3 through DNA Hypermethylation Is Associated with Lymph Node Metastasis in Gastric Carcinomas - Peng, Dun-Fa (Public Library of Science, 2012)
Gastric cancer remains the second leading cause of cancer-related death in the world. H. pylori infection, a major risk factor for gastric cancer, generates high levels of reactive oxygen species (ROS). Glutathione peroxidase 3 (GPX3), a plasma GPX member and a major scavenger of ROS, catalyzes the reduction of hydrogen peroxide and lipid peroxides by reduced glutathione. To study the expression and gene regulation of GPX3, we examined GPX3 gene expression in 9 gastric cancer cell lines, 108 primary gastric cancer samples and 45 normal gastric mucosa adjacent to cancers using quantitative real-time RT-PCR. Downregulation or silencing of GPX3 was detected in 8 of 9 cancer cell lines, 83% (90/108) gastric cancers samples, as compared to non-tumor adjacent normal gastric samples (P<0.0001). Examination of GPX3 promoter demonstrated DNA hypermethylation (≥10% methylation level determined by Bisulfite Pyrosequencing) in 6 of 9 cancer cell lines and 60% of gastric cancer samples (P = 0.007). We also detected a significant loss of DNA copy number of GPX3 in gastric cancers (P<0.001). Treatment of SNU1 and MKN28 cells with 5-Aza-2′ Deoxycytidine restored the GPX3 gene expression with a significant demethylation of GPX3 promoter. The downregulation of GPX3 expression and GPX3 promoter hypermethylation were significantly associated with gastric cancer lymph node metastasis (P = 0.018 and P = 0.029, respectively). We also observed downregulation, DNA copy number losses, and promoter hypermethylation of GPX3 in approximately one-third of tumor-adjacent normal gastric tissue samples, suggesting the presence of a field defect in areas near tumor samples. Reconstitution of GPX3 in AGS cells reduced the capacity of cell migration, as measured by scratch wound healing assay. Taken together, the dysfunction of GPX3 in gastric cancer is mediated by genetic and epigenetic alterations, suggesting impairment of mechanisms that regulate ROS and its possible involvement in gastric tumorigenesis and metastasis.